1972
DOI: 10.4319/lo.1972.17.4.0570
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL AND ISOTOPIC EVIDENCE FOR THE IN SITU ORIGIN OF MARINE HUMIC SUBSTANCES1,2

Abstract: Humic and fulvic acids were extracted from marine and nonmarine Recent sediments and from soils, These acids are shown to be major components of the organic matter from marine and nonmarine sediments-some marine sediments may contain 70% of their organic carbon in the hmnic and fulvic acid fraction.Marine and terrestrial humic acids have similar carbon and hydrogen content, but the former generally contain more sulfur and nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
85
0
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(89 citation statements)
references
References 17 publications
2
85
0
1
Order By: Relevance
“…Analysis of sedimentary HM fi-om coastal and littoral environments shows that the precipitated HM is deposited in the sediment (Nissenbaum and Kaplan 1972). A crude idea about the magnitude of the acidification signal in the investigated estuary (Topdal Fjord, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of sedimentary HM fi-om coastal and littoral environments shows that the precipitated HM is deposited in the sediment (Nissenbaum and Kaplan 1972). A crude idea about the magnitude of the acidification signal in the investigated estuary (Topdal Fjord, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of HM relative to total sedimentary organic matl;er (sedimentary organic C, not reported here, multiplied bly 1 .S) was 11% in the surface sediments and 16% in the deepest sample. Nissenbaum and Kaplan (1972) showed that in marine sediments, the sum of humic and fulvic acids can constitute 4-68% of the sedimentary organic C. In recent sediments from the Blake-Bahamas basin, Tanner basin, Walvis Bay, and Guayamas basin, humic acids constitute 12.8,2.7, 13.7, and 15-29% of the total sedimentary organic C (Stuermer et al 1978;Simonett et al 1979). The proportion of HM (isolated at pH 2 following extraction with pyrophosphate/NaOH) in surface sediments (O-5 cm) from the Baltic Sea ranges from 3 to 20% of the total organic matter (Poutanen 1985).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wakesman, 1933; King, 1971, Ishiwatari, 1971;Nissenbaum and Kaplan, 1972;Bordovsky, 1965;Degens et al, 1964;Jackson, 1975.) Humic substances constitute the largest fraction of the organic matter in soils and modern sediments.…”
Section: -Soil and Sedimentary Humic Substancesmentioning
confidence: 99%
“…Soil and sedimentary humic substances show differences in elemental composition, specific density, functional groups, and products produced upon oxidative or reductive degradation which suggest differences in structure and a more aromatic character for the soil humic substances (Ishiwatari, 1971; Nissenbaum and Kaplan, 1972;Huc and Durand, 1974;Rashid and King, 1970;Ishiwatari, 1969). These investigations have demonstrated that humic substances are produced by decomposition and resynthesis in both soils and sediments, however, differences in the sources of organic matter and the properties of the environment influence the structural features of the final products.…”
Section: -Soil and Sedimentary Humic Substancesmentioning
confidence: 99%